Dengue knowledge, practices, and Aaedes Larval populations in selected low and high dengue priority areas in Miag-ao, Iloilo - VML/ess 3.20.17.; T-UG 1798. (2009.)
This cross-sectional study aimed to compare the knowledge, practices, and Aedes larval populations between low and high dengue priority areas of Miag-ao, Iloilo. Larval surveys were done to determine aedes larval populations, expressed as House Index (HI), Container Index (CI), and Breteau Index (BI).
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Dengue fever